2018
DOI: 10.1002/aet2.10124
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Bias Education and Emergency Medicine Training: Step One? Awareness

Abstract: Objective: Prior research suggests that health care providers are susceptible to implicit biases, specifically prowhite biases, and that these may contribute to health care disparities by influencing physician behavior. Despite these findings, implicit bias training is not currently embedded into emergency medicine (EM) residency training and few studies exist that evaluate the effectiveness of implicit bias training on awareness during residency conference. We sought to conduct a mixed-methods program evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 13 publications
2
59
0
Order By: Relevance
“…The fact that we found effects on our participants' information-processing but not decisionmaking is consistent with prior work suggesting that many medical practitioners are already aware of the need to ensure that bias does not contaminate their judgments (Green et al, 2007;Tsai & Michelson, 2017). In fact, bias training and other interventions designed to enhance racial sensitivity appear to be prevalent in hospitals throughout the United States (e.g., Tsai & Michelson, 2017) and evidence suggests they can be effective (e.g., Devine et al, 2012;FitzGerald et al, 2019;Zeidan et al, 2019). Our findings suggest that it might be beneficial to expand existing training to address the potential for racial bias in the context of child abuse cases.…”
Section: Discussionsupporting
confidence: 87%
“…The fact that we found effects on our participants' information-processing but not decisionmaking is consistent with prior work suggesting that many medical practitioners are already aware of the need to ensure that bias does not contaminate their judgments (Green et al, 2007;Tsai & Michelson, 2017). In fact, bias training and other interventions designed to enhance racial sensitivity appear to be prevalent in hospitals throughout the United States (e.g., Tsai & Michelson, 2017) and evidence suggests they can be effective (e.g., Devine et al, 2012;FitzGerald et al, 2019;Zeidan et al, 2019). Our findings suggest that it might be beneficial to expand existing training to address the potential for racial bias in the context of child abuse cases.…”
Section: Discussionsupporting
confidence: 87%
“…These cases were all in regional under‐resourced communities, with Gowa's case being the most significant in terms of remoteness 7–9 . Together with the lack of clinical information this has been shown to result in implicit racial bias 11 . Because of the retrospective nature of these cases, we are unable to make any accurate conclusions about patient perceptions of discrimination; however, it was indicated that Naomi was dissatisfied with her care prior to her death 7 .…”
Section: Discussionmentioning
confidence: 92%
“…It fails to recognise individual patient characteristics, dynamic interactions and institutional context factors that may lead a clinician to make certain management decisions. The use of clinical vignettes may not accurately reflect the decisions made in the ED where physician fatigue, patient burden, time pressures and lack of clinical information may result in prejudiced patient management 2,11 . Clinical vignettes may also be prone to response bias, where participants provide a more socially desirable response than what they would do in clinical practice 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Emergency medicine and family medicine have seen improvements by implementing the aforementioned action items. 13 , 14 …”
Section: Directions Moving Forward: Strategies To Create An Antiracismentioning
confidence: 99%
“… 11 , 12 Most plastic surgery training programs’ curricula lack implicit bias and cultural competency training when compared with other specialties (family medicine, emergency medicine, etc.). 13 , 14 Finally, access and equitable care has come into question regarding post mastectomy breast reconstruction rates, cleft lip and palate care, and even body contouring rates regarding black and brown communities. 6 , 8 , 15 Although the etiology of these disparities is complex and multifactorial, systemic and structural racism is a significant factor.…”
Section: Introductionmentioning
confidence: 99%